Method for preparing porous carbon for supercapacitor from biomass and plastic
By adding waste plastic to waste biomass raw materials, the pore structure and defect degree of porous carbon materials are regulated, and the problem of low energy density of existing supercapacitors is solved, and the preparation of porous carbon materials with high capacitance and high power is achieved.
Patent Information
- Application Number
- CN202411978039.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The low energy density of existing supercapacitors has limited its application and development. How to obtain high capacitance and high power supercapacitor carbon materials in a simple and low-cost way is a huge challenge.
By adding waste plastic to waste biomass raw materials, the coordinated carbon-promoting effect between the two substances and the strong interaction in the carbonization process can be used to regulate the pore structure, defect degree and microstructure in situ to prepare porous carbon materials with high specific surface area and high pore volume.
It is achieved without additional activator to obtain a multi-stage porous carbon material with a specific surface area of 1059.55 m2·g-1, and its mass specific capacitance can reach 197.7 F·g-1 (0.1 A·g-1) and 153.9 F·g-1 (1 A·g-1), and significantly improve the capacity and rate performance of the supercapacitor.
Smart Images

Figure CN119637868A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of comprehensive resource utilization and capacitor materials, and specifically relates to a method for preparing porous carbon materials from biomass and plastics and the application of the porous carbon in electrode materials for supercapacitors. Background Art
[0002] With the rapid development of various electronic devices, electrical devices and new energy vehicles, advanced energy storage equipment is urgently needed. At the same time, clean energy such as solar energy, wind energy, tidal energy, etc. cannot be directly connected to the power grid due to their large fluctuations. This requires high-performance and high-capacity energy storage devices to be fully integrated with the power grid system. Among the existing energy storage technologies, supercapacitors have great potential and value in the future energy system due to their fast charging and discharging characteristics and long cycle life.
[0003] At present, there are two mechanisms for storing energy in supercapacitors. One is the double-layer capacitor represented by carbon-based materials, which relies on the physical attraction between ions and electrode surfaces, so its capacitance mainly depends on the surface properties and pore size distribution accessible to ions. The other is based on the pseudocapacitor principle of metal oxides, and energy storage is generated through a reversible Faraday charge reaction process. In fact, regardless of which mechanism, the electrode materials in supercapacitors play an important role in electrochemical performance, which has prompted researchers to actively develop high-performance new electrode materials to meet the growing needs of emerging technologies. However, current supercapacitors exhibit low energy density, which has led to a bottleneck in the application and development of supercapacitors. How to obtain supercapacitor carbon materials with high capacitance and better high power performance from multiple angles in a simple and low-cost way is a huge challenge.
[0004] Among the electrode materials used, porous carbon materials have the characteristics of short ion transmission distance, low resistance, and charge storage density, and have been proven to be an ideal electrode material for supercapacitors. Biomass-derived carbon materials are currently the main raw materials for porous carbon preparation because they can inherit the unique structure, renewability, and environmental protection characteristics of the precursor. The preparation of biomass porous carbon often requires alkali, acid, water vapor, CO 2or obtained by a template method. Patent CN102431993A discloses a method for preparing a porous carbon material using rice husk as a carbon source. The invention uses zinc chloride as an activator and microwave-assisted heating to obtain a mesoporous carbon material, which has good rate performance when used in supercapacitors. Patent CN112794324A discloses a porous carbon material with high mesoporosity, in which lignin and alkali carbonate are first hydrothermally treated, followed by carbonization and activation. Patent CN109485029A discloses a layer-by-layer self-assembled lignin / oxalate complex prepared by layer-by-layer self-assembly of lignin and oxalate, followed by carbonization and acid washing to obtain a porous carbon material. The porous carbon material of this invention is 200-1500 m 2 ·g -1 , pore volume 0.5-1.5 cm 3 / g, and its application in supercapacitors shows 320 Fg -1 Although there have been many studies / patents reporting on this, these technologies often face the disadvantages of complex processes, high costs, and low specific surface area and mesopore ratio of carbon materials. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing porous carbon for supercapacitors from biomass and plastics. By adding waste plastics to waste biomass raw materials, the synergistic carbon-promoting effect between the two substances and the strong interaction during the carbonization process are utilized to in-situ regulate the pore structure, defect degree and microstructure. In addition, using waste biomass and waste plastics as raw materials can achieve the purpose of preparing high-performance porous capacitor carbon with a simple and low-cost technology, and complete the environmental protection measure of resource recycling.
[0006] The technical solution provided by the present invention is as follows:
[0007] A method for preparing porous carbon for supercapacitors from biomass and plastics, comprising the following steps:
[0008] The biomass and plastic are crushed, sieved and dried, and the mixed raw materials are gradually heated to a first temperature under an inert atmosphere and maintained for a period of time to obtain a pre-carbonized material, the pre-carbonized material and an activator are mixed, and activated and pore-formed at a second temperature under an inert atmosphere to obtain a carbon material, and the carbon material is acid-washed, washed with water and dried to obtain porous carbon; the second temperature is higher than the first temperature.
[0009] Furthermore, the biomass is one or more of corn straw, rice straw, wheat straw, poplar, pine, chemical lignin, organic solvent lignin, sulfate lignin, and alkali lignin; the plastic is one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyethylene terephthalate; and the mass ratio of biomass to plastic is 1~9:0~9.
[0010] Furthermore, the activator is ZnCl 2 , H 3 PO 4 、Na 2 CO 3 、NaHCO 3 , NaOH, K 2 CO 3 , KHCO 3 , KOH or more; the acid used for pickling is one or more of sulfuric acid, nitric acid, and hydrochloric acid.
[0011] Furthermore, the inert atmosphere is one of high-purity nitrogen, high-purity argon, and high-purity helium.
[0012] Furthermore, the first temperature is 400~600°C, the holding time of the first temperature is 0.5~5h, and the speed of rising to the first temperature is 0.5~20°C / min; the second temperature is 700~900°C, the holding time of the second temperature is 0.5~5h, and the speed of rising to the second temperature is 0.5~20°C / min.
[0013] Furthermore, the mass ratio of the pre-carbonized material to the activating agent is 1:0~3.
[0014] Furthermore, the biomass and plastic are mixed by one or more of stirring wet mixing, dry material ball milling mixing, and dry material roller mixing.
[0015] The present invention also provides porous carbon prepared by the above method.
[0016] The present invention also provides the use of the porous carbon in preparing an electrode sheet, wherein the electrode sheet is prepared by coating the porous carbon as claimed in claim 8, a conductive agent and a binder on nickel foam.
[0017] Furthermore, the mass ratio of the porous carbon, the conductive agent and the binder is 8:1:1.
[0018] A method for preparing porous carbon for supercapacitors from biomass and plastics, comprising the following steps:
[0019] (1) Crush, screen and dry various raw materials;
[0020] (2) mixing two or more different types of materials processed in the above step (1) in a certain proportion;
[0021] (3) heating the material obtained in step (2) to 400-600°C at a heating rate of 0.5-20°C / min under an inert atmosphere and maintaining the temperature for 0.5-5h to promote pre-carbonization of the material;
[0022] (4) The pre-carbonized material in step (3) is further activated to form pores, wherein the activation and forming pores are performed in any of the following ways:
[0023] 1) The pre-carbonized material is activated to form pores at a temperature of 700-900°C in an inert environment;
[0024] 2) Mix the pre-carbonized material with the activator in an inert environment at a temperature of 700-900°C to activate and form pores;
[0025] (5) acid-washing, water-washing and drying the carbon material obtained in the above step (4) to finally obtain a porous carbon material;
[0026] In step (1) of the present invention, the particle size of the raw material screening is 80-200 mesh;
[0027] In step (1) of the present invention, the drying temperature is 60-120° C. and the drying time is 12-48 h;
[0028] In step (1) of the present invention, the raw materials are one or more of biomass and plastics, wherein the biomass materials are one or more of corn straw, rice straw, wheat straw, poplar, pine, chemical lignin, organic solvent lignin, sulfate lignin, and alkali lignin, and the plastic materials are one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyethylene terephthalate.
[0029] Furthermore, the mixed substances in step (2) of the present invention are two or more of the above materials, preferably alkali lignin and polyethylene terephthalate. The mixing method in step (3) of the present invention is one or more of stirring wet mixing, dry material ball milling mixing, and dry material roller mixing, preferably dry material roller mixing.
[0030] Furthermore, in step (3) of the present invention, the mixing time is 0.5 to 8 hours.
[0031] In step (3) of the present invention, the inert atmosphere is one of high-purity nitrogen, high-purity argon and high-purity helium.
[0032] The heating rate for further heating in step (4) of the present invention is 10°C / min.
[0033] The activation time in step (4) of the present invention is 0.5 to 4 h.
[0034] The mixing method with the activator in step (4) of the present invention is one or more of dry material ball milling, dry material roller mixing, and stirring wet mixing, wherein the solvent for wet mixing is an aqueous solution, and the preferred mixing method is stirring wet mixing.
[0035] Furthermore, the activator is ZnCl 2 , H 3 PO 4 、Na 2 CO 3 、NaHCO 3 , NaOH, K 2 CO 3 , KHCO 3 , KOH or more, preferably KOH.
[0036] Furthermore, the mixing time is 0.5 to 8 h, preferably 6 h.
[0037] The acid used in the pickling in step (5) of the present invention is one or more of sulfuric acid, nitric acid and hydrochloric acid, preferably hydrochloric acid.
[0038] Furthermore, the water washing in step (5) of the present invention specifically comprises repeatedly washing with deionized water until the deionized water after washing is neutral.
[0039] Furthermore, in step (5) of the present invention, the drying temperature is 80-160° C. and the drying time is 12-24 h.
[0040] Beneficial Effects
[0041] The present invention promotes the generation of carbon through the synergistic effect between biomass and plastic, selectively regulates the pore structure and defect degree, and forms a porous carbon material with high specific surface area and high pore volume. At the same time, its defect degree can be controlled between 0.50 and 1.00 (measured by Raman spectroscopy). G / I D Indicates the degree of defect) shows excellent energy storage performance.
[0042] The preparation method of the present invention comprises physically mixing dried biomass raw materials such as alkaline lignin and waste plastics such as PET in a certain mass ratio to obtain a powder mixture, pre-carbonizing under the protection of an inert atmosphere, and performing a secondary activation treatment on the obtained material to obtain a porous carbon material. The present invention is a simple, low-cost, universal, and efficient high-quality porous carbon material for application in supercapacitors. Without adding an additional activator, a specific surface area of 1059.55 m 2 ·g -1The mass specific capacitance of the multi-level porous carbon material can reach 197.7 F g -1 (0.1 A g -1 ) and 153.9 F·g -1 (0.1 A g -1 ). By adjusting the appropriate activator, a specific surface area of 2857.70 m 2 ·g -1 The mass specific capacitance of the multi-level porous carbon material can reach 310.5 F·g -1 (0.1 A g -1 ) and 237.8 F·g -1 (1 A g -1 ).
[0043] The present invention uses biomass resources and waste plastics as raw materials, takes the carbon-promoting mechanism between biomass and plastics as the core, and through simple carbonization and activation processes, can selectively adjust the pore structure and specific surface area of carbon materials to obtain high specific surface area porous carbon materials. Compared with traditional activated carbon materials, it is beneficial to further improve the capacity and rate performance of supercapacitors. In addition, the present invention converts waste into energy storage materials, has significant environmentally friendly advantages, is more conducive to reducing pollution emissions and enhancing resource utilization, and is expected to become a process technology for achieving energy conservation and emission reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a scanning electron microscope image of the hierarchical porous carbon material prepared in Example 2;
[0045] Figure 2 The Raman spectra of the hierarchical porous carbon materials of Examples 2 and 7 and Comparative Examples 1 and 2;
[0046] Figure 3 is a nitrogen adsorption-desorption curve diagram of Example 2;
[0047] Figure 4 is a nitrogen adsorption-desorption curve diagram of Example 7;
[0048] Figure 5 It is the constant current charge and discharge diagram under different current densities of Example 2;
[0049] Figure 6 The constant current charge and discharge diagrams at different current densities of Example 7;
[0050] Figure 7 The cyclic voltammograms at different scan rates of Example 2;
[0051] Figure 8 The cyclic voltammograms at different scan rates of Example 7 are shown in FIG. DETAILED DESCRIPTION
[0052] In order to more clearly illustrate the technical solution of the present invention, the present invention will be further described below; obviously, the following description is only a part of the embodiments, and for ordinary technicians in this field, without paying creative work, the technical solution of the present invention can also be applied to other similar scenarios based on these; in order to more clearly illustrate the technical solution of the present invention, the technical solution of the present invention is further described in detail below.
[0053] Example 1
[0054] Step 1: PET (polyethylene terephthalate) and alkaline lignin are crushed separately, and then sieved to obtain particles with a size of 80-100 mesh, and the particles are placed in an oven at 80°C for drying for 24 hours;
[0055] Step 2: Weigh 7 g of treated alkaline lignin and 3 g of PET and mix them through a roller mixer. During the mixing, add a certain amount of spherical zirconium oxide beads to ensure sufficient tumbling mixing of the raw materials;
[0056] Step 3: Place the mixed raw materials in the constant temperature zone of a tube furnace, introduce high-purity nitrogen at a flow rate of 50 mL / min, increase the temperature from room temperature to 600°C at a heating rate of 2°C / min, and stay at 600°C for 2 h for pre-carbonization;
[0057] Step 4: The pre-carbonized material was heated to 900°C at a heating rate of 10°C / min and kept for 2 h to promote further carbonization and pore formation, and then naturally cooled to room temperature to obtain a carbon material;
[0058] Step 5: The carbon material obtained in step 4 is acid-washed with 2 M hydrochloric acid, filtered, and then washed with distilled water until neutral, and then placed in an oven at 105° C. to dry, thereby obtaining a porous carbon material;
[0059] Step 6: The porous carbon material is mixed and coated on nickel foam in a ratio of active material (porous carbon material): conductive agent (acetylene black): binder (polyvinylidene fluoride) = 8:1:1 to prepare an electrode sheet, and tested in 6 MKOH electrolyte;
[0060] The specific surface area obtained in this example is 949.29 m 2 ·g -1 The micro-mesopore volume is 1.17 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 69.2% of micro-mesopores. G / I DThe value is 0.77, and the mass specific capacitance of the material reaches 177.8 F·g -1 (0.1 A g -1 ) and 143.0 F·g -1 (1 A g -1 ).
[0061] The high specific surface area and rich pore structure are due to the overflow of small molecular products during the high temperature process. On the other hand, the alkaline substances in the alkaline lignin act as activators to react with carbon at a higher second temperature, promoting the further formation of pores.
[0062] Example 2
[0063] The hierarchical porous carbon material was prepared in the same manner as in Example 1, except that the mass of the alkaline lignin and the PET in step 2 of Example 1 was replaced with 5 g:5 g.
[0064] The specific surface area obtained in this example is 1059.55 m 2 ·g -1 , micro-mesopore volume is 1.44cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 74.3% of micro-mesopores. G / I D The value is 0.82, and the mass specific capacitance of the material reaches 197.7 F·g -1 (0.1 A g -1 ) and 153.9 F·g -1 (1 A g -1 ).
[0065] The appropriate ratio of biomass to plastic is crucial, as it affects the strength of the two in the reconstruction of carbon materials and the synergistic effect of promoting carbon formation during pyrolysis. When no additional activator is used, a ratio of 5:5 is the best ratio in the implementation case of this patent. Figure 1 The microstructure of the carbon material is displayed, and the existence of pore structure can be clearly observed on its surface. Figure 2 The defect level of the carbon material is shown. With the addition of plastic PET, the primary products of its pyrolysis condense and cross-link with the primary products of pyrolysis of lignin, reconstructing the carbon and adjusting its defect level. Figure 3 N is the carbon material 2 Physical adsorption-desorption curves show that the large amount of nitrogen adsorption at low pressure indicates the existence of microporous structure, and the appearance of hysteresis loops indicates that the surface of carbon materials has mesoporous structure. Higher specific surface area and more micro-mesopores further improve its energy storage performance. Figure 5The charge and discharge curves of the carbon material at different current densities show that the negative electrode material has an ideal capacitance behavior and has a high energy storage performance. According to the charge and discharge curve analysis, the mass specific capacitance of the material reaches 197.7F·g-1 (0.1 A·g-1) and 153.9 F·g-1 (1 A·g-1). The CV curves ( Figure 7 ) show a nearly ideal rectangular shape, further demonstrating the capacitive properties and ultrafast response of the prepared carbon material.
[0066] Example 3
[0067] The hierarchical porous carbon material was prepared in the same manner as in Example 1, except that the mass of the alkaline lignin and the mass of the PET in step 2 of Example 1 was replaced with 3 g:7 g.
[0068] The specific surface area obtained in this example is 550.20 m 2 ·g -1 The micro-mesopore volume is 0.46 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 54.3% of the micro-mesopores. G / I D The value is 0.87, and the mass specific capacitance of the material reaches 101.2 F·g -1 (0.1 A g -1 ) and 86.9 F·g - (1 A g -1 ).
[0069] Compared with Examples 1, 2 and Comparative Example 1, the specific surface area and pore volume of the carbon material obtained in Example 3 are not superior, but the energy storage performance is excellent. On the one hand, this material has relatively more micropores, and on the other hand, it has relatively more carbon defects that provide sites for adsorbing ions.
[0070] Example 4
[0071] The hierarchical porous carbon material was prepared using the same method as in Example 1, except that the initial heating rate in step 3 in Example 1 was changed to 20° C. / min.
[0072] The specific surface area obtained in this example is 723.52 m 2 ·g -1 The micro-mesopore volume is 1.14 cm 3 ·g -1 , hierarchical porous carbon materials in which mesopores account for 92.3% of the micromesopores.
[0073] Compared with the carbon material obtained in Example 1, the carbon material obtained in Example 4 has a higher proportion of mesopores. At a higher heating rate, the substances volatilized by pyrolysis of biomass and plastic quickly impact the carbon material, and the secondary reactions of biomass and plastic in a shorter time are less. Ultimately, the carbon material has fewer micropores and more mesopores.
[0074] Example 5
[0075] The porous carbon material was prepared using the same method as in Example 1, except that the initial heating rate in step 3 in Example 1 was changed to 10° C. / min.
[0076] This example obtains a specific surface area of 754.34 m 2 ·g -1 , micro-mesopore volume is 1.20cm 3 ·g -1 , hierarchical porous carbon materials in which mesopores account for 90.8% of micropores.
[0077] Compared with the carbon material obtained in Example 1, the carbon material obtained in Example 5 has a higher proportion of mesopores. At a higher heating rate, the substances volatilized by pyrolysis of biomass and plastics quickly impact the carbon material, and the secondary reactions of biomass and plastics in a shorter time are less. Ultimately, the carbon material has fewer micropores and more mesopores. In this patent, a heating rate of 2°C / min is more conducive to the formation of porous carbon.
[0078] Comparative Example 1
[0079] The porous carbon material was prepared using the same method as in Example 1, except that the raw materials in step 2 in Example 1 were all replaced by alkaline lignin.
[0080] The specific surface area of this comparative example is 814.87 m 2 ·g -1 The micro-mesopore volume is 0.55 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 83.6% of micro-mesopores. G / I D The value is 0.17, and the mass specific capacitance of the material reaches 77.3F·g -1 (0.1 A g -1 ) and 90.3 F·g -1 (1 A g -1 ).
[0081] The specific surface area and pore volume of the carbon material obtained in Comparative Example 1 are lower than those of the carbon material obtained in Example 1, which indicates that the addition of PET can effectively adjust the specific surface area of the carbon material and improve the pore structure.
[0082] Comparative Example 2
[0083] The porous carbon material was prepared using the same method as in Example 1, except that all the raw materials in step 2 in Example 1 were replaced by PET.
[0084] The specific surface area of this comparative example is 6.47 m 2 ·g -1 The micro-mesopore volume is 0.03 cm 3 ·g -1 , mesopores account for 95.7% of the carbon material in the micro-mesopores. G / I D The value is 1.09, and the mass specific capacitance of the material is 11.8F·g -1 (0.1 A g -1 ) and 2.6 F·g -1 (1 A g -1 ).
[0085] Compared with the example of adding alkaline lignin, when the raw material is only PET, the specific surface area and pore volume of the obtained carbon material are smaller, and its energy storage performance is lower than that of the carbon material prepared by mixing the two. PET does not contain alkaline substances that can act as an activator and non-network structure, so the activation and pore-forming effect under high temperature conditions is poor.
[0086] Example 6
[0087] In the steps of the original embodiment 3, the carbon material obtained in step 3 is mixed with the activator, and the specific steps are: the carbon material and potassium hydroxide are weighed respectively according to a mass ratio of 1:1, the potassium hydroxide is first dissolved in distilled water, the carbon material is placed in the potassium hydroxide aqueous solution and mixed and stirred for 6 hours, then heated at 80°C to evaporate the water, after evaporating the water, it is transferred to a 105°C oven for further drying and dehydration for 24 hours, the dehydrated mixture is placed in a tube furnace, and the temperature is increased to 850°C at a heating rate of 10°C / min and stayed for 2 hours, and then naturally cooled to room temperature. The remaining steps are the same as those in embodiment 3.
[0088] The specific surface area of this example is 1,240.45 m 2 ·g -1 The micro-mesopore volume is 0.76 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 37.4% of micro-mesopores. G / I D The value is 0.86, and the mass specific capacitance of the material is 185.3 F·g -1 (0.1 A g -1 ) and 164.9 F·g -1 (1 A g-1 ).
[0089] Compared with Example 3, the carbon material obtained in Example 6 has a higher specific surface area and better energy storage performance. During the second temperature treatment, an additional activator is added, and the reaction between the activator and carbon activates and forms pores in the carbon material, thereby further obtaining a carbon material with a high specific surface area.
[0090] Example 7
[0091] The porous carbon material was prepared using the same method as in Example 7, except that the mass ratio of the carbon material to potassium hydroxide in Example 6 was changed to 1:3.
[0092] The specific surface area obtained in this example is 2,857.70 m 2 ·g -1 The micro-mesopore volume is 2.22 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 40.6% of the micro-mesopores. G / I D The value is 0.94, and the mass specific capacitance of the material is 310.5 F·g -1 (0.1 A g -1 ) and 237.8 F·g -1 (1 A g -1 ).
[0093] Compared with other embodiments, embodiment 7 shows the best energy storage performance. During the second temperature treatment, an activator is added, and the mass ratio of carbon material to potassium hydroxide is 1:3 activator, and finally a porous carbon material with ultra-high specific surface area and a carbon material with certain defects are obtained, which is beneficial to the energy storage of ions.
[0094] Figure 4 This is the nitrogen physical adsorption-desorption curve of carbon material. The large amount of nitrogen adsorption at low pressure indicates the existence of microporous structure, and the appearance of hysteresis loop indicates that the surface of carbon material has mesoporous structure. Figure 6 The charge and discharge curves of carbon materials at different current densities show that the highly linear behavior and almost symmetrical shape of the negative electrode material prove that the negative electrode material has ideal capacitance behavior and has high energy storage performance. According to the charge and discharge curve analysis, the mass specific capacitance of the material reaches 1310.5 F·g -1 (0.1 A g -1 ) and 237.8 F·g -1 (1 A g -1 ). CV curves acquired at increasing scan rates from 5 to 100 mV / s ( Figure 8) show a nearly ideal rectangular shape with a larger internal area, further demonstrating the capacitive properties and ultrafast response of the prepared carbon material.
[0095] Example 8
[0096] A porous carbon material was prepared using the same method as in Example 7, except that the activation temperature in Example 7 was changed to 900°C.
[0097] The specific surface area obtained in this example is 1920.73 m 2 ·g -1 The micro-mesopore volume is 1.77 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 48.3% of micro-mesopores. G / I D The value is 1.10, and the mass specific capacitance of the material is 232.2 F·g -1 (0.1 A g -1 ) and 183.6 F·g -1 (1 A g -1 ).
[0098] Compared with Example 7, the carbon material obtained in Example 8 has a lower specific surface area and a lower mass specific capacitance. The second activation temperature actually affects the pore structure of the carbon material. Higher temperatures are conducive to the reaction of potassium hydroxide with the carbon material, resulting in the conversion of more micropores to mesopores. However, this will cause a relative reduction in micropores and specific surface area, as well as the collapse of some macropores and mesopores.
[0099] Example 9
[0100] A porous carbon material was prepared using the same method as in Example 7, except that the activation temperature in Example 9 was changed to 800°C.
[0101] The specific surface area obtained in this example is 2,539.96 m 2 ·g -1 The micro-mesopore volume is 1.67 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 36.0% of micro-mesopores. G / I D The value is 1.00, and the mass specific capacitance of the material is 252.9 F·g -1 (0.1 A g -1 ) and 219.2 F g -1 (1 A g -1 ).
[0102] Compared with Example 7, the specific surface area of the carbon material obtained in Example 9 is reduced, and the mass specific capacitance is also reduced. Different second activation temperatures actually affect the pore structure of the carbon material, and a temperature of 800°C will produce an activation pore-forming effect. It is crucial to select a suitable activation pore-forming temperature. In this patent, in the additional method of adding an activator at the second temperature, the temperature of 850°C is more conducive to forming a porous carbon material for supercapacitors.
[0103] Comparative Example 3
[0104] The porous carbon material was prepared using the same method as in Example 6, except that the raw material in step 2 in Example 6 was replaced by alkaline lignin.
[0105] The specific surface area of this comparative example is 1403.71 m 2 ·g -1 The micro-mesopore volume is 1.87 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 66.8% of micro-mesopores. G / I D The value is 0.91, and the mass specific capacitance of the material reaches 117.1F·g -1 (0.1 A g -1 ) and 103.6 F·g -1 (1 A g -1 ).
[0106] Compared with Example 7, the carbon material obtained in Comparative Example 3 has a lower specific surface area and a smaller mass specific capacitance. When the raw material is only alkaline lignin, even if a small amount of activator is added during the second temperature activation process, the pores will be expanded, which can be seen from the pore volume compared with Comparative Example 1. However, this is accompanied by the loss of carbon material and the further expansion of the pores is not conducive to the adsorption of ions.
[0107] Comparative Example 4
[0108] The porous carbon material was prepared using the same method as in Example 7, except that PET was used as the raw material in step 2 of Example 7.
[0109] The specific surface area of this comparative example is 3263.60 m 2 ·g -1 The micro-mesopore volume is 1.70 cm 3 ·g -1 , a multi-level porous carbon material in which mesopores account for 16.3% of micro-mesopores. G / I D The value is 1.12, and the mass specific capacitance of the material reaches 292.6F·g -1 (0.1 A g-1 ) and 232.2 F g -1 (1 A g -1 ).
[0110] Compared with Example 7, Comparative Example 4 obtains the carbon material with the highest specific surface area. However, the mass specific capacitance of the carbon material is smaller, and its energy storage performance is inferior to that of Example 7. The carbon material obtained in Comparative Example 4 has a smaller proportion of mesopores, and it is relatively more difficult for ions to enter the micropores, that is, there are fewer accessible micropores. Excellent supercapacitor electrode materials require an appropriate proportion of micro-mesoporous pores. On the other hand, and also a key point, the completely amorphous carbon structure does not promote the localization of charge at defect sites, resulting in a weakened interaction between ions and carbon and an inability to better adsorb ions.
[0111] Comparative Example 5
[0112] The carbon material was prepared using the same method as in Example 3, except that step 4 in Example 3 was not performed.
[0113] The specific surface area of this comparative example is 27.14 m 2 ·g -1 The micro-mesopore volume is 0.13 cm 3 ·g -1 , mesopores account for 99.1% of the carbon material in the micro-mesopores, and the I G / I D The value is 0.88, and the mass specific capacitance of the material reaches 13.1F·g -1 (0.1 A g -1 ) and 5.6 F·g -1 (1 A g -1 ).
[0114] The above results show that the second temperature activation is necessary. The carbon material without the second temperature is not completely carbonized at 600°C, and only some pores are formed.
[0115] Comparative Example 6
[0116] The carbon material was prepared using the same method as in Example 3, except that the heating rate in step 3 in Example 3 was replaced by 20°C / min, the temperature was 900°C, and step 4 was not performed.
[0117] The specific surface area of this comparative example is 525.60 m 2 ·g -1 The micro-mesopore volume is 0.61 cm 3 ·g -1 , the mesopores account for 73.1% of the carbon material in the micro-mesopores. G / I DThe value is 0.95, and the mass specific capacitance of the material reaches 83.7F·g -1 (0.1 A g -1 ) and 65.3 F·g -1 (1 A g -1 ).
[0118] The above results show that the main role of staying at the first temperature is pre-carbonization and promoting the secondary reaction of biomass and plastic to reconstitute new carbon materials. Staying at the first temperature will also promote the formation of more micropores. Direct treatment at 900°C will cause the rapid volatilization of volatile substances during pyrolysis to impact the surface structure of the carbon material to form more mesopores. It should be noted that shorter treatment time and higher temperature will retain part of the original structure of the biomass, which is also the cause of more mesoporous structure.
[0119] Comparative Example 7
[0120] The carbon material obtained on the basis of Example 3 is further mixed with an activator and activated at high temperature to form pores. Specifically, the carbon material and potassium hydroxide obtained in Example 3 are weighed in a mass ratio of 1:3, the potassium hydroxide is first dissolved in distilled water, the carbon material is placed in a potassium hydroxide aqueous solution and mixed and stirred for 6 hours, then heated at 80°C to evaporate the water, and after evaporating the water, it is transferred to a 105°C oven for further drying and dehydration for 24 hours, and the dehydrated mixture is placed in a tubular furnace, heated to 850°C at a heating rate of 10°C / min and stayed for 2 hours, and then naturally cooled to room temperature. Subsequently, it is pickled with 2M hydrochloric acid, filtered and washed with distilled water until neutral, and then placed in a 105°C oven for drying to obtain a porous carbon material.
[0121] The specific surface area of this comparative example is 1102.73 m 2 ·g -1 , micro-mesopore volume is 1.50 cm 3 ·g -1 , a carbon material in which mesopores account for 70.0% of the micro-mesopores, and the I G / I D The value is 0.90, and the mass specific capacitance of the material reaches 186.9 F·g -1 (0.1 A g -1 ) and 156.0 F·g -1 (1 A g -1). When the carbon material treated at the second temperature is activated and pore-formed with an activator, the carbon material is difficult to be activated to obtain a higher specific surface area, even if a higher proportion of the activator has been added. Combined with Comparative Examples 4, 6, and 7, the technical advantages of the first temperature pre-carbonization and the higher second temperature activation in this patent are once again demonstrated, and porous carbon materials used in supercapacitors can be easily prepared.
[0122] The present invention forms a carbon material with a certain degree of defects by re-condensing and cross-linking the pyrolysis products of biomass and plastic at high temperature, and improves the degree of defects of the material by adjusting the raw material ratio, so as to promote the adsorption of ions at the defects. In addition, the biomass and plastic mixture is used as raw materials, and the pre-carbonization at the first temperature and the activation pore formation at the second temperature are used to achieve the regulation of the specific surface area and the pore structure. The presence of the plastic component effectively increases the microporous structure of the adsorbed ions, adjusts the micro-mesoporous ratio of the carbon material, and the appropriate amount of mesopores promotes the faster transmission of ions and transfer to the micropores. Without adding an additional activator, in Example 2, that is, the ratio of biomass to plastic is 5:5, the first temperature (pre-carbonization temperature) is 600°C, the heating rate is 2°C / min, and the second temperature is 900°C. The prepared carbon material shows the best energy storage performance under the same conditions, and the specific surface area, micro-mesoporous ratio and degree of defects of the carbon material are more suitable for supercapacitors. In the case of using an activator, in Example 7, that is, the ratio of biomass to plastic is 3:7, the first temperature (pre-carbonization temperature) is 600°C, the heating rate is 2°C / min, the second temperature is 850°C, the activator is potassium hydroxide, and the ratio of pre-carbonized material to activator is 1:3, the prepared carbon material exhibits the best energy storage performance in this patent. This is due to the higher specific surface area, suitable micro-mesopore ratio and a certain degree of defects of the carbon material.
Claims
1. A method for preparing porous carbon for supercapacitors from biomass and plastics, characterized in that: The steps include: The biomass and plastic are crushed, sieved and dried, and the mixed raw materials are gradually heated to a first temperature under an inert atmosphere and maintained for a period of time to obtain a pre-carbonized material, the pre-carbonized material and an activator are mixed, and activated and pore-formed at a second temperature under an inert atmosphere to obtain a carbon material, and the carbon material is acid-washed, washed with water and dried to obtain porous carbon; the second temperature is higher than the first temperature.
2. The method for preparing porous carbon for supercapacitor from biomass and plastic according to claim 1, characterized in that: The biomass is one or more of corn stalks, rice stalks, wheat stalks, poplar, pine, chemical lignin, organic solvent lignin, sulfate lignin, and alkali lignin; the plastic is one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyethylene terephthalate; and the mass ratio of biomass to plastic is 1~9:0~9.
3. The method for preparing porous carbon for supercapacitor from biomass and plastic according to claim 1, characterized in that: The activator is one or more of ZnCl2, H3PO4, Na2CO3, NaHCO3, NaOH, K2CO3, KHCO3, and KOH; the acid used in the pickling is one or more of sulfuric acid, nitric acid, and hydrochloric acid.
4. The method for preparing porous carbon for supercapacitor from biomass and plastic according to claim 1, characterized in that: The inert atmosphere is one of high-purity nitrogen, high-purity argon and high-purity helium.
5. The method for preparing porous carbon for supercapacitor from biomass and plastic according to claim 1, characterized in that: The first temperature is 400~600℃, the holding time of the first temperature is 0.5~5h, and the speed of rising to the first temperature is 0.5~20℃ / min; the second temperature is 700~900℃, the holding time of the second temperature is 0.5~5h, and the speed of rising to the second temperature is 0.5~20℃ / min.
6. The method for preparing porous carbon for supercapacitor from biomass and plastic according to claim 1, characterized in that: The mass ratio of the pre-carbonized material to the activator is 1:0~3.
7. The method for preparing porous carbon for supercapacitor from biomass and plastic according to claim 1, characterized in that: The biomass and plastic are mixed by one or more of stirring wet mixing, dry material ball milling mixing, and dry material roller mixing.
8. A porous carbon, characterized in that: Prepared by the method according to any one of claims 1 to 7.
9. The use of the porous carbon according to claim 8 in preparing an electrode sheet, characterized in that: The electrode sheet is prepared by coating the porous carbon, conductive agent and adhesive as described in claim 8 on foamed nickel.
10. The use according to claim 9, characterized in that: The mass ratio of porous carbon, conductive agent and binder is 8:1:1.
Citation Information
Patent Citations
Method for preparing mesoporous carbon material for electrochemical capacitor by using rice hulls as raw materials
CN102431993A
Lignin porous carbon nanosheet as well as preparation method thereof and application in supercapacitor electrode material
CN109485029A
High-mesoporous-rate lignin hierarchical pore carbon material and preparation method and application thereof
CN112794324A
Method for rapidly preparing enzymatic-lignin-base nitrogen-rich activated carbon through radio frequency plasma modification
CN107089659A
Preparation of lignin nano-carbon fibers for supercapacitor
CN107956001A